2020
DOI: 10.2147/cmar.s231901
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pre/Post-Treatment Dynamic of Inflammatory Markers Has Prognostic Value in Patients with Small Hepatocellular Carcinoma Managed by Stereotactic Body Radiation Therapy</p>

Abstract: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are inflammatory indexes that may reflect immune response to tumors and prognosis. We investigated the prognostic values of pre-treatment and post-treatment NLR and PLR and changes in those ratios in patients with small hepatocellular carcinoma (sHCC) treated with stereotactic body radiation therapy (SBRT). Patients and methods: Sixty patients who received SBRT were retrospectively reviewed. NLR and PLR were calculated by division … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In another study by Zhuang et al, a decrease in circulating blood cells was noted in 50 patients receiving SBRT of 48-60 Gy for small HCC. 24 Although not addressed statistically, the lymphocyte counts had a larger decline (dropping by nearly half the pretreatment value) compared to other cells. We also found that the differential radiation response of immune cells leads to a significantly elevated NLR and PLR post-SBRT.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In another study by Zhuang et al, a decrease in circulating blood cells was noted in 50 patients receiving SBRT of 48-60 Gy for small HCC. 24 Although not addressed statistically, the lymphocyte counts had a larger decline (dropping by nearly half the pretreatment value) compared to other cells. We also found that the differential radiation response of immune cells leads to a significantly elevated NLR and PLR post-SBRT.…”
Section: Discussionmentioning
confidence: 92%
“…SBRT is well known as an extremely precise, highdose form of radiation therapy (RT) targeting a relatively small region encompassing the tumors while avoiding normal tissues from clinically intolerable radiation exposure. However, even with the favourable property of sharp dose fall-off and small field size compared to conventionally fractionated radiotherapy, SBRT still produces a certain degree of systemic effects on peripheral blood components during a course of limited fractionations for patients with lung, 23 pancreas, 18 and liver 12,24 cancers. In vivo and in vitro investigations showed that human peripheral blood cells differ in their radiosensitivity, with lymphoid cells being extremely radiosensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zheng et al have carried out a meta-analysis and reported that an elevated pre-treatment level of NLR or PLR indicated poor outcomes for HCC patients 47 . However, Kinoshita et al, Zhang et al and Zhuang et al believed that pre-treatment NLR and PLR are not correlated to the survival of HCC 22 , 48 , 49 . Our research identified the prognostic factors on HBV-related small solitary HCC since the small HCC patients enrolled in our study were limited to solitary nodule and HBV infection as the only etiological factor.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of serum inflammation indicators before treatment for liver cancer has been confirmed by studies focus on surgical resection, liver transplantation, target therapy, radiofrequency ablation (RFA),transcatheter arterial chemoembolization (TACE) and selective internal radiation therapy (SIRT) 16 - 21 . However, studies about cases of liver cancer treated with SBRT rarely reported prognostic inflammatory markers, instead, most of which merely focused on NLR and PLR 22 . This article hopes to develop visualized multivariate predictive nomograms and identify more possible novel prognostic indicators for SBRT therapy in hepatitis B-related small solitary HCC by reviewing the existing data.…”
Section: Introductionmentioning
confidence: 99%